Program for Optimizing the Role of WPA to Reduce the Stigma and Discrimination PLWHA in The Community - Sri Winarni; Wiwin MARTININGSIH (Health Notions, 2020)
Stigma and discrimination remain significant obstacles in the management of HIV / AIDS prevention programs. The data shows there are stigma and discrimination within the health service, treatment is not going well. PLWHA tends to be ashamed and afraid to control or get medicine in the hospital, injustice to the provision of services, thus, low quality of care, and lack of respect for patients. The purpose of this study was to reduce the stigma and discrimination of HIV / AIDS patients in the community, through community empowerment programs. Long-term benefits were finding the right design to reduce stigma and discrimination toward HIV / AIDS patients, through community empowerment by integrating the concepts of social support, social networks, and social marketing. One group pretest-posttest design was used in this research. Seventy-five respondents were taken purposively. The intervention was "Optimizing Program of WPA's Role in reducing stigma and discrimination toward HIV AIDS patients in the community". The results showed that before and after the intervention, the average of community members did not have a negative attitude, did not perceived discrimination, and supported the equity. However, there were still hesitant and had a negative attitude within several community members to HIV / AIDS patient and the numbers decreased after the intervention. Based on the Wilcoxon signed-rank test, there were significant differences in negative attitudes, perceived discrimination, and support for equity before and after intervention with significance levels respectively p = 0.049, p = 0.006, and p = 0.000. Intensive coordination and evaluation of activities are needed to ensure the sustainability of the WPA Optimization program. Keywords: WPA optimization program; stigma; discrimination; HIV / AIDS